2020
DOI: 10.1002/wcc.690
|View full text |Cite
|
Sign up to set email alerts
|

Is solar geoengineering ungovernable? A critical assessment of governance challenges identified by the Intergovernmental Panel on Climate Change

Abstract: Solar radiation modification (SRM) could greatly reduce climate change and associated risks. Yet it has not been well‐received by the climate change expert community. This is evident in the authoritative reports of the Intergovernmental Panel on Climate Change (IPCC), which emphasize SRM's governance, political, social, and ethical challenges. I find seven such challenges identified in the IPCC reports: that SRM could lessen mitigation; that its termination would cause severe climatic impacts; that researching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Other methods are solar radiation management (SRM) or albedo modification and infrared radiation management (IRM), which aims at increasing the outgoing infrared radiation emitted by the Earth and atmosphere into outer space [191,192]. The last two methods consist of purposely modifying the energy balance in the atmosphere to reduce or cancel out part of the climatic consequences of the current ACC according to a specific metric such as the surface air temperature, precipitation, or others [51,190,193]. The mitigation urgency to reach the 1.5 • C goal of the Paris Agreement requires the implementation of a variety of negative emission processes [194].…”
Section: Sai Geoengineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Other methods are solar radiation management (SRM) or albedo modification and infrared radiation management (IRM), which aims at increasing the outgoing infrared radiation emitted by the Earth and atmosphere into outer space [191,192]. The last two methods consist of purposely modifying the energy balance in the atmosphere to reduce or cancel out part of the climatic consequences of the current ACC according to a specific metric such as the surface air temperature, precipitation, or others [51,190,193]. The mitigation urgency to reach the 1.5 • C goal of the Paris Agreement requires the implementation of a variety of negative emission processes [194].…”
Section: Sai Geoengineeringmentioning
confidence: 99%
“…Models have been developed to optimize the levels of SAI geoengineering against climate change and economic conditions projected for 2050 using the SSP baseline scenarios [222]. Despite these developments, the IPCC did not include SAI geoengineering as a possible policy measure to reach the 1.5 • C Paris Agreement target [14], a position that has been harshly criticized [193]. Horton [223] considers that SAI geoengineering has been hampered by the fear of unilateralism in its implementation and presents various mechanisms that encourage collaboration between states.…”
Section: Sai Geoengineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence (Petersen, 2018) and treatment of climate engineering in IPCC reports, specifically the Fifth Assessment Report (AR5), has already been the subject of controversy and critique (Parker and Geden, 2016;Beck and Mahony, 2018;Reynolds, 2021). Baskin (2019) has traced how the topic of geoengineering moved from taboo to being a topic for consideration first as an emergency response and then, eventually, as an economically efficient, pre-emptive approach to climate change.…”
Section: The Role and Meaning Of Environmentmentioning
confidence: 99%
“…In March 2021, for instance, a report by a committee of the US National Academy of Sciences concluded that the United States should establish, ideally in international collaboration, a research program to assess the feasibility of solar geoengineering as a stopgap measure for addressing anthropogenic climate change (National Academies of Sciences, Engineering, and Medicine, 2021). Individual researchers in the United States have called for a globally organized “mission‐driven research program” on solar geoengineering (Morrow, 2020) and for a special IPCC report on this topic (Reynolds, 2021). Harvard University has set up a Solar Geoengineering Research Program that plans among others a Stratospheric Controlled Perturbation Experiment to study the behavior of stratospheric aerosols.…”
Section: Introductionmentioning
confidence: 99%